The Hopf Bifurcation for an Abstract Functional Differential Equation and Its Application (Journal of Partial Differential Equations, 1990)
ln this peper we obtained the Hopf bifurcation theorem for an abstract functional differential equation by the results of [1]. The asymptotic expression of bifurcation formulae and stability condition were given in detail. Applying the result, we considered the Hopf bifurcation problem for a reaction-diffusion equation with time delay.
Keywords: Hopf bifurcation; Functional differential equation